Religion, science and near-death experiences (2025)
Near-death experiences (NDEs) are remarkable events in the lives of the people who have had such experiences, which leave major impacts on their personal beliefs. Over the years, various explanations have emerged for NDEs, ranging from scientific to religiously driven elucidations. While scientists suggest the subjective nature of NDEs, which are traceable to disturbances in bodily multisensory integration during life threatening events, religious beliefs which revolve around the afterlife align with many NDEs. This paper seeks to explore the phenomenon of NDE from the perspectives of religion and science to find the intersection between the two fields. This is with the view of offering a holistic understanding of the experience. The study focuses on the intricate interplay between scientific explanations and religious or spiritual interpretations of Near-Death Experiences (NDEs). It concludes that by striking a balance between these varying perspectives, one can gain a more comprehensive understanding of NDEs, acknowledging both their scientific underpinnings and their profound impact on spiritual and metaphysical realms.